2016
DOI: 10.1590/0037-8682-0089-2016
|View full text |Cite
|
Sign up to set email alerts
|

Candida arthritis in a patient diagnosed with spondyloarthritis

Abstract: Candida arthritis is an unusual manifestation that usually affects the knees. A 35-year-old man presented with a 2-month history of pain and swelling in the right knee. Swelling persisted after anti-infl ammatory treatment. Peripheric spondyloarthritis was considered, but methotrexate, sulfasalazine, and methylprednisolone did not reduce the swelling. Direct examination of synovial fl uid and a culture were positive for Candida albicans. Intravenous and intra-articular amphotericin-B were administered. The art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
2
0
3
Order By: Relevance
“…Our study found seven cases with primary fungal knee septic arthritis, which is very rarely described in literature (Taxy and Kodros, 2005;Dewar and Sigler, 2010;Gamaletsou et al, 2012;Lee et al, 2012;Lu et al, 2012;Jeong et al, 2013;Miller et al, 2015;Cevik et al, 2016). It usually occurs as a result of accidental implantations of fungus during traumatic procedures, such as surgery, and is usually reported in patients with predisposing factors such as immunosuppression, malignancy, and drug abuse (Lee et al, 2012).…”
Section: Surgery Combined With Long-term Antifungal Treatment Achieve...mentioning
confidence: 53%
See 1 more Smart Citation
“…Our study found seven cases with primary fungal knee septic arthritis, which is very rarely described in literature (Taxy and Kodros, 2005;Dewar and Sigler, 2010;Gamaletsou et al, 2012;Lee et al, 2012;Lu et al, 2012;Jeong et al, 2013;Miller et al, 2015;Cevik et al, 2016). It usually occurs as a result of accidental implantations of fungus during traumatic procedures, such as surgery, and is usually reported in patients with predisposing factors such as immunosuppression, malignancy, and drug abuse (Lee et al, 2012).…”
Section: Surgery Combined With Long-term Antifungal Treatment Achieve...mentioning
confidence: 53%
“…Common routes of infection include direct inoculation, contiguous spread, and hematogenous dissemination ( Miller et al., 2015 ). FOI resulting from fungemia, skin lesion, or trauma was rarely reported ( Taxy and Kodros, 2005 ; Dewar and Sigler, 2010 ; Lee et al., 2012 ; Lu et al., 2012 ; Jeong et al., 2013 ; Cevik et al., 2016 ), while FOIs secondary to orthopedic surgeries were more commonly seen in literature, especially in implant-related cases. Implant-related fungal infections, typically fungal periprosthetic joint infection (PJI) after hip/knee arthroplasty, was even more difficult to diagnose and treat for the reason of biofilm formation on the bioprosthetic surfaces ( Cobo et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…[42] 2016 1 Kadın/68 Dirsek C. parapsilosis Romatoid artrit CAS→ FLK İyileşme Çevik ve ark. [43] 2016 1…”
Section: Mi̇ka→ Flkunclassified
“…Los principales sitios afectados son articulaciones (rodilla, cadera y húmero), se suele asociar a intervenciones invasivas como artroplastias. 1 C. albicans ocupa más de 40% de las candidiasis, seguida de C. parapsilosis y C. glabrata. 2,3 Los factores de riesgo predisponentes son uso de esteroides, uso crónico de antibióticos de amplio espectro, inmunosupresión y artritis reumatoide.…”
Section: Introductionunclassified
“…2,3 Los factores de riesgo predisponentes son uso de esteroides, uso crónico de antibióticos de amplio espectro, inmunosupresión y artritis reumatoide. 1,4 Los síntomas más frecuentes son dolor, edema e hipertermia. 3 El cuadro clínico suele ser de inicio insidioso y evolución lenta, por esta razón el diagnóstico se puede retrasar, llevando a complicaciones como coinfección bacteriana, amputación y muerte.…”
Section: Introductionunclassified